Proteksi Katodik Metoda Anoda Tumbal Untuk Mengendalikan Laju Korosi - S, Fitri Afriani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Metal structures are more increasingly used in modern industry. The absence of control or pour control of the corrosion control system, metal structures directly related to the water will be succeptible to corrosion, prevention of corrosion in the marine environment based on the principle of cathodic protection is necessary. Principle of cathodic is protection system on metal surface by means of direct current adequate to the metal surface and convert all of the surface area of the anode becomes cathodic area. This research aims to study the effect of cathodic protection corrosion control, determine and choose the type of anode, size of anode, and number of anode the efficient in use to protect the corrosion. The research plan is conducted with take variation about type of anode such as aluminium mixture and zinc mixture, the size variation of anode and number of anode that are anode and two anode to protect one anode in sea water system and gambut water. Data processing is done by using MPY calculation. In this research to decrease the corrosion rate of steel is better using two amounts of anode from aluminium mixture than using zink mixture in sea water media, similarly the gambut water. The corrosion rate of steel in sea water without cathodic protection is 4,5657 MPY and in gambut water is 3,9445 MPY. Corrosion rate could be decreased to 1,0511 MPY by using two amounts of aluminium mixture with surface area 49,6 cm2 and 1,7704 MPY using two amounts of zink mixture with surface area 49,6 cm2 in sea water and 0,6915 MPY using two amounts of aluminium mixture with surface area 49,6 cm2, and 1,0511 MPY using zink mixture with surface area 49,6 cm2 in gambut water. Keywords : aluminium mixture, cathodic protection, sacrificial anode, zink mixture